Multimodal sensing and active continuous closed‐loop feedback for achieving reliable manipulation in the outdoor physical world. Issue 1 (28th November 2018) - Chan, Wesley P.; Mizohana, Hiroto; Chen, Xiangyu; Shiigi, Yasuto; Yamanoue, Yoshiyuki; Nagatsuka, Masaki; Inaba, Masayuki
Abstract: The use of field robots can greatly decrease the amount of time, effort, and associated risk compared to if human workers were to carryout certain tasks such as disaster response. However, transportability and reliability remain two main issues for most current robot systems. To address the issue of transportability, we have developed a lightweight modularizable platform named AeroArm. To address the issue of reliability, we utilize a multimodal sensing approach, combining the use of multiple sensors and sensor types, and the use of different detection algorithms, as well as active continuous closed‐loop feedback to accurately estimate the state of the robot with respect to the environment. We used Challenge 2 of the 2017 Mohammed Bin Zayed International Robotics Competition as an example outdoor manipulation task, demonstrating the capabilities of our robot system and approach in achieving reliable performance in the fields, and ranked fifth place internationally in the competition.